(untitled) (Annals of Bangladesh Agriculture, 2022)
Onion (Allium cepa) is one of the most important spices in Bangladesh. It suffers from various diseases from seedbed to field. Purple blotch (Alternaria porri) and white blotch (Stemphylium vesicarium) simultaneously attack the crop, causing a purple blotch complex. To assess locally available onion cultivars for response to purple blotch complex and yield performance, a three-year experiment was conducted in the net house and research field of Sher-e-Bangla Agricultural University, Dhaka, during the winter of 2010-11, 2011-2012 and 2012-2013. Fourteen onion cultivars, namely BARI Piaz-1, BARI Piaz-2, BARI Piaz-3, BARI Piaz-4, BARI Piaz-5, Taherpuri, Indian hybrid, Lal Teer onion seed, Masud onion seed, Thakurgoan local, Faridpur local, Manikgong local, Indian big and Indian small were used in the experiment. Among the evaluated cultivars, BARI Piaz-3 showed the lowest disease incidence and severity and the maximum bulb yield, followed by BARI Piaz-2 and Indian big. The disease incidence, severity, and yield for BARI Piaz-3 were 54.45-36.33%, 5.75-12.01%, and 10.97-13.89 t/ha, while the corresponding values for BARI Piaz-2 were 41.49, 44.01, and 7.28-10.79 t/ha, respectively. In contrast, Indian big had disease incidence, severity, and yield values of 36.52-58.79%, 15.43-22.96%, and 8.41-10.60 t/ha, respectively. Therefore, the cultivar BARI Piaz -3 and 2 may be recommended for extension of cultivation.Ann. Bangladesh Agric. (2021) 25 (2) : 37-46